Religious and Moral Values Learning Based on Integration-Interconnection in Early Childhood Education - Dwi Hastuti; Shomiyatun Shomiyatun (Early Publishing, 2026)
Religious and moral values (RMV) form one of the six developmental domains that must be nurtured from an early age, yet ECE institutions in practice still tend to deliver RMV instruction separately from other domains such as science, language, art, and social life, leaving religious values understood mainly through text and memorisation rather than internalised behaviour. This article conceptually examines how the integration-interconnection paradigm popularised by M. Amin Abdullah can be adapted as a learning framework for RMV in ECE. Using a library research method, this study reviewed accredited national and international journal articles and books on the topic. The findings show that integration-interconnection in ECE RMV learning is best realised through a thematic-holistic strategy that weaves spiritual values into science, art, language, and social activities via storytelling, role-play, habituation, and digital media, supported by close collaboration between educators and parents. This study recommends an integrated curriculum that removes the dichotomy between religious and general education from an early age. Unlike earlier work, which treats integration-interconnection as a higher-education discourse or discusses RMV strategies in isolation from it, this article's novelty lies in synthesising both bodies of literature into a single thematic-holistic framework tailored to ECE in the digital era.